(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In article, the author submits a philosophical, psychological substantiation and generalization of results of pedagogical experiment on introduction to educational practice of pedagogical system of self-organizing of pupils and students a yak of means of self-development of the person.